Software module for capturing and tracking moving targets - Hladka, Olena; Karpovich, Ivan; Tymrakevych, Anastasiia (Modeling, Control and Information Technologies: Proceedings of International scientific and practical conference, 2025)
Software for drones has been created that allows tracking objects in real time. A software module has been developed that provides automatic capture and tracking of moving targets. The developed software uses computer vision algorithms and machine learning technologies. The object tracking mechanism has been integrated using CSRT or KCF trackers. An algorithm for automatic image scaling taking into account target movement has been implemented. Video stream processing has been optimized to ensure stable tracking of object movement in real time. Interactive control of the tracking process using control keys has been implemented.